Social Technology: An Interdisciplinary Approach to Improving Care for Older Adults - Kleinman, Arthur; Chen, Hongtu; Levkoff, Sue E.; Forsyth, Ann; Bloom, David E.; Yip, Winnie; Khanna, Tarun; Walsh, Conor J.; Perry, David; Seely, Ellen W.; Kleinman, Anne S.; Zhang, Yan; et al. (Frontiers in Public Health, 2021)
Population aging is a defining demographic reality of our era. It is associated with an increase in the societal burden of delivering care to older adults with chronic conditions or frailty. How to integrate global population aging and technology development to help address the growing demands for care facing many aging societies is both a challenge and an opportunity for innovation. We propose a social technology approach that promotes use of technologies to assist individuals, families, and communities to cope more effectively with the disabilities of older adults who can no longer live independently due to dementia, serious mental illness, and multiple chronic health problems. The main contributions of the social technology approach include: (1) fostering multidisciplinary collaboration among social scientists, engineers, and healthcare experts; (2) including ethical and humanistic standards in creating and evaluating innovations; (3) improving social systems through working with those who deliver, manage, and design older adult care services; (4) promoting social justice through social policy research and innovation, particularly for disadvantaged groups; (5) fostering social integration by creating age-friendly and intergenerational programs; and (6) seeking global benefit by identifying and generalizing best practices. As an emergent, experimental approach, social technology requires systematic evaluation in an iterative process to refine its relevance and uses in different local settings. By linking technological interventions to the social and cultural systems of older people, we aim to help technological advances become an organic part of the complex social world that supports and sustains care delivery to older adults.